The Role of Enlightened Leadership in Achieving Organizational Excellence: An Analytical Study of the Opinions of a Sample of Workers in a Number of Private Hospitals in the City of Sulaymaniyah - كمال رشيد, نيان; بکر حمە, ژینۆ (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
This study aims to determine the impact of the role of enlightened leadership in its dimensions (the role models, the role of the developer, the role of servant, the role of the changer, the role of the visionary) in achieving organizational ingenuity in its dimensions (exploiting of opportunities, exploring of opportunities) by analyzing the opinions of a sample of workers in some private hospitals in Sulaymaniyah city. The problem of the study was identified by asking the main question: What is the impact of the dimensions of enlightened leadership on achieving organizational ingenuity in some private hospitals in Sulaymaniyah city? In order to reach the answer, the study included a set of sub-questions to achieve the main and sub-objectives of the study, and to reach those goals, a group of studies and scientific sources were adopted to determine the dimensions of the study variables and formulate their hypotheses. As for the practical side, the study used the analytical descriptive approach to describe the study variables and analyze its hypotheses using the Statistical Packages for Social Sciences program (SPSS 25). The number of distributed questionnaires was (175), and the number of retrieved forms was (155), and after excluding incomplete forms, the final number of forms valid for analysis was (144). The study reached a set of conclusions, the most important of which is the existence of a statistically significant effect of enlightened leadership in its dimensions (the role models, the role of developer, the role of servant, the role of the changer, the role of the visionary) in achieving organizational ingenuity in its dimensions (exploiting of opportunities, exploring of opportunities). Based on the foregoing, the study presented a set of suggestions, the most important of which is checking the quality of services provided by hospitals on an ongoing basis through the use of scientific methods, benefiting from observations and feedback provided by beneficiaries of hospital services, and coordination between the hospitals under study with the aim of exchanging experiences and benefiting from the strengths available in Each hospital in addressing weaknesses in the services provided by the hospitals under study, and using scientific methods such as interviews and questionnaires and collecting qualitative and quantitative information in analyzing the external environment of hospitals and benefiting from them in exploring new opportunities for developing the work of the hospitals under study.